ҚАЗАҚСТАНДАҒЫ ҚЫТАЙ ДИАСПОРАСЫНЫҢ ҚАЛЫПТАСУЫ ЖӘНЕ ОЛАРДЫҢ ӘЛЕУМЕТТІК ЖАҒДАЙЫ (Journal of Oriental Studies, 2016)
В этой статье описывается переселение в Казахстанпервых китайских мигрантов, становление китайскойдиаспоры в Казахстане, их социальное положение иместо в нынешнем Казахстанском обществе.The name of article is “Formation of Chinese Diasporain Kazakhstan and it’s social position in society”. As thetitle implies, the article describes the main stages of Chinesemigration to Kazakhstan, formation of Chinese Diasporaand their social position in nowadays Kazakhstan society.